Teacher Pedagogical Competence Development Workshop for Strengthening Student Character and Achievement Motivation - Asrin, Asrin; Sukarso, AA; Fahruddin, Fahruddin; Sunarti, Dian (Unram Journal of Community Service, 2024)
This workshop aims to improve teachers' pedagogical competence in strengthening students' character and achievement motivation. Strong pedagogical competence is an important foundation for teachers to be able to teach effectively and build students' character. This workshop involved a series of interactive sessions that included discussions related to the application of innovative learning techniques that focus on building students' character. This workshop was held at SDN 1 Ampenan, Mataram City and was attended by teachers and principals. From the results of the evaluation of this workshop activity, it received a positive response from all participants who attended. Most teachers also stated that this workshop provided new insights related to pedagogical competence which was considered very relevant to increasing student engagement. In addition, this evaluation also showed the need for further mentoring and periodic training so that implementation can run more optimally in the classroom